Achieving Hepatitis C Micro-Elimination in Chinese Injecting Drug Users: A Dynamic Network Modeling Study - Ying Chen; Yun Bao; Mengxia Yan; Huajie Jin; Kaijie Yao; Chi Zhang; Wen Li; Bin Wu (Infectious Diseases and Therapy)
Abstract Introduction The World Health Organization (WHO) has established objectives for eradicating the hepatitis C virus (HCV). People who inject drugs (PWID), a major driver of HCV transmission, are an essential part of China’s hepatitis C elimination program. This study aimed to estimate the requisite screening and antiviral treatment levels to achieve these goals among people who inject drugs in China and identify the most cost-effective strategy. Methods This study utilized models based on dynamic social networks to simulate HCV transmission and disease progression among people who inject drugs in China, incorporating a cost-effectiveness analysis from a healthcare perspective. Results To achieve the WHO targets, a minimum screening and treatment rate of 10% is required to meet the mortality goal, while a 25% rate is necessary for the incidence goal. The most cost-effective strategy includes a 25% screening rate and a 95% treatment rate. Compared to no intervention, this approach significantly reduces costs by − $85,873.38 (95% CI  − $94,311.16 to  − $77,435.59) and adds 24.66 (95% CI 23.68 to – 25.64) quality-adjusted life years. The intervention is dominant, with a cost-effectiveness ratio of − $3482.29 (95% CI  − $3982.73 to  − $3020.11) per quality-adjusted life year. Conclusion Achieving the WHO’s hepatitis C virus elimination targets among people who inject drugs in China is feasible and cost-saving.